Magnetic code disc material and preparation method thereof, and magnetic encoder

By using Au layers on both sides of the FeCrCoMoTi magnetic film to form a double Au catalytic magnetic layer structure and vacuum annealing, the problem of insufficient coercive force of the existing FeCrCo magnetic film is solved, and the coercive force is significantly enhanced, the preparation process is simplified and cost reduction is achieved.

CN119900002AActive Publication Date: 2025-04-29JIHUA LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510392021.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The coercive force of the existing FeCrCo magnetic films is difficult to meet the needs of high-performance applications, and the existing improvement methods have problems such as complex process, high cost or limited effect.

Method used

A double Au catalytic magnetic layer structure is used, and the FeCrCoMoTi film is tightly clamped by using an Au layer on both sides and vacuum annealing to form a fine "sandwich structure" to improve the coercivity of the film.

Benefits of technology

The coercive force of FeCrCoMoTi magnetic film is significantly improved, and the coercive force increases to 552 Oe, and the preparation process is simple and efficient, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900002A_ABST
    Figure CN119900002A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal magnetic thin film materials, and particularly discloses a magnetic code disc material, a preparation method and a magnetic encoder, the magnetic code disc material comprises a double-Au catalytic magnetic layer and a Ta layer, and the double-Au catalytic FeCrCoMoTi magnetic layer comprises a first Au layer, a FeCrCoMoTi layer and a second Au layer; the FeCrCoMoTi magnetic code disc material is further subjected to vacuum annealing at the temperature of 645 DEG C to 655 DEG C. The invention further provides a specific preparation method of the magnetic code disc material and a magnetic encoder comprising the magnetic code disc material. According to the magnetic code disc material comprising the double-Au catalytic FeCrCoMoTi magnetic force layer, the preparation process is simple, compared with a traditional FeCrCoMoTi thin film, the coercive force of the magnetic code disc material is obviously increased, meanwhile, the preparation process is simple and efficient, and cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of metal magnetic films, and specifically relates to a magnetic code disk material and a preparation method, and a magnetic encoder. Background Art

[0002] As a new type of position detection element, magnetic encoders have shown great application potential in the fields of industrial automation, robotics, new energy vehicles, etc., with their significant advantages such as non-contact measurement, strong anti-pollution ability, and good environmental adaptability. As the core component of the magnetic encoder, the performance of the magnetic code disk directly affects the accuracy, resolution, and stability of the encoder.

[0003] In recent years, with the continuous advancement of materials science and manufacturing technology, the research on magnetic code disk materials has also made significant progress. FeCrCo film (in some cases, it also includes a small amount of other elements, such as Mo and Ti, etc., generally referred to as FeCoCr film or FeCrCo film) is an important magnetic material and is widely used in magnetic storage, sensors and other fields. However, the magnetic properties of FeCrCo films, especially coercivity, are often difficult to meet the needs of high-performance applications. In the prior art, the magnetic properties of the film are usually improved by means of graded heat treatment, doping or interface engineering, but these methods often have problems such as complex processes, high costs or limited effects. Therefore, how to improve the coercivity of FeCrCo magnetic films is one of the key issues in the field of magnetic film research. Summary of the invention

[0004] The purpose of this application is to solve the deficiencies of the prior art and provide a magnetic code disk material and preparation method, and a magnetic encoder, which specifically adopts the following technical solutions: First, the present application provides a magnetic code disk material, including a double Au catalytic magnetic layer and a Ta layer; the double Au catalytic magnetic layer is obtained by vacuum annealing a first Au layer, a FeCrCoMoTi layer and a second Au layer from bottom to top; the vacuum annealing temperature is 645°C-655°C.

[0005] In this application, in order to improve the coercivity of FeCrCoMoTi magnetic code disk material as much as possible while maintaining a relatively simple preparation method, the applicant has determined a technical solution of using double Au layers to catalyze FeCrCoMoTi through unremitting scientific research and exploration.

[0006] The applicant found that by using Au layers on both sides of the FeCrCoMoTi film to tightly clamp the FeCrCoMoTi, the surface active element Au is used as a catalyst attached to both sides of the FeCrCoMoTi layer, thereby forming a fine and thin "sandwich structure", which can form a unique catalytic effect on FeCrCoMoTi; during the heat treatment process (i.e., vacuum annealing process), the Au atoms in the Au layers on both sides of the FeCrCoMoTi in the "sandwich structure" diffuse into the boundary of the FeCrCoMoTi layer, so that the surface free energy of the FeCrCoMoTi layer is reduced. In this process, the α phase inside the FeCrCoMoTi film is catalyzed by the Au layers sandwiched on both sides during the spinodal decomposition process, and the Au layer provides an additional driving force for the spinodal decomposition of FeCrCoMoTi, so that during the spinodal decomposition process, the α phase inside the FeCrCoMoTi layer is decomposed into a strong magnetic phase rich in Fe and Co (α1 phase) and a weak magnetic phase rich in Cr (α2 phase), which greatly improves the magnetic properties of the material.

[0007] Moreover, during this process, when Au atoms diffuse into the FeCrCoMoTi phase boundary, the grains are refined while the particle separation is improved. This is mainly attributed to the synergistic effect of Au in the above-mentioned catalytic spinodal decomposition process, in which the function of grain boundary modification is also produced; grain boundary modification promotes defect healing, which makes the lattice distortion caused by the size difference between Au atoms and matrix atoms in the Au layer in this application pin dislocations, reduce lattice defect density, and improve crystal integrity.

[0008] As a further improvement of the above technical solution, the thickness of the first Au layer is 5nm-10nm. The thickness of the second Au layer is 5nm-10nm.

[0009] After continuous experimental research and theoretical exploration, the applicant found that the selection of an Au layer of appropriate thickness as the catalytic layer on both sides of the FeCrCoMoTi layer is of great significance: after rapid annealing, the Au atoms in the Au layer diffuse into the FeCrCoMoTi layer, which not only refines the grains of the FeCrCoMoTi layer, but also improves the separation of the particles in the FeCrCoMoTi layer, thereby reducing the FeCrCoMoTi grain size while reducing the exchange coupling between the FeCrCoMoTi particles, so that the gaps between these grains can serve as channels for rapid atomic diffusion, thereby greatly improving the coercivity of the film.

[0010] On the other hand, the applicant also found that when the thickness of the Au layer is greater than 10 nm, the cost increases while the technical effect does not improve accordingly, because the excessive thickness of the catalytic layer will lead to excessive Au atoms, and excessive Au atoms will cause the gap between the grains in the FeCrCoMoTi layer to decrease, which is not conducive to sufficient diffusion and will make it difficult to improve the coercive force of the film.

[0011] On the other hand, in the present application, Au, as a surface active element, can serve as a catalyst to promote the decomposition of α-phase stripes inside the FeCrCoMoTi film. This is because Au has a lower surface energy (lower than Fe, Co and Cr elements). After rapid annealing, the diffusion of Au atoms into the boundary of the FeCrCoMoTi phase will reduce the free energy of the film surface, thereby increasing the coercive force; and when the thickness of the Au layer is less than 5 nm, its catalytic effect is not obvious.

[0012] As a further improvement of the above technical solution, the thickness of the FeCrCoMoTi layer is 90nm-110nm, the thickness of the Ta layer is 5nm-10nm, and the mass ratio of Fe, Cr, Co, Mo and Ti in the FeCrCoMoTi layer is 42:30:25:2:1.

[0013] Secondly, the present application also provides a specific preparation method of the above magnetic code disk material, comprising the following steps: Prepare a substrate, perform DC sputtering on the substrate, and then perform vacuum annealing to obtain a magnetic code disk material; the DC sputtering includes the following processes: perform a first DC sputtering on the substrate to prepare a first Au layer, then perform a second DC sputtering to prepare a FeCrCoMoTi layer, then perform a third DC sputtering to prepare a second Au layer, and then perform a fourth DC sputtering to prepare a Ta layer.

[0014] As a further improvement of the above technical solution, the vacuum degree during DC sputtering is: 1×10-5Pa -3 ×10 -5 Pa; the first DC sputtering time was 46.2s, the second DC sputtering time was 1785.7s, the third DC sputtering time was 46.2s, and the fourth DC sputtering time was 66.7s.

[0015] As a further improvement of the above technical solution, the vacuum annealing conditions are 645°C-655°C and the time is 5min-10min.

[0016] Finally, the present application also provides a magnetic encoder using the above-mentioned magnetic code disk material.

[0017] The beneficial effects of the present application are as follows: the magnetic code disk material provided by the present application, including a double Au-catalyzed FeCrCoMoTi magnetic layer, has a significantly increased coercive force compared to the traditional FeCrCoMoTi film, and at the same time the preparation process is simple, efficient, and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Shown is the MH curve diagram of Example 1; Figure 2 Shown is the MH curve diagram of Comparative Example 1; Figure 3 Shown is the MH curve diagram of Comparative Example 2. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of this application, so as to fully understand the purpose, scheme and effect of this application. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0020] Example 1 First, this embodiment provides a magnetic code disk material, which includes, from bottom to top: a double Au catalytic magnetic layer, which is obtained by vacuum annealing a first Au layer with a thickness of 5 nm, a FeCrCoMoTi layer with a thickness of 100 nm, a second Au layer with a thickness of 5 nm, and a Ta layer with a thickness of 5 nm from bottom to top; the vacuum annealing temperature is 650°C.

[0021] The preparation method of the magnetic code disk material provided in this embodiment is: (1) 316 non-magnetic stainless steel code disc is selected as the metal substrate material (i.e., substrate). In a magnetron sputtering device, a DC sputtering method is used to deposit the code disc at 3×10 -5 The first Au layer was deposited on the substrate at a vacuum degree of Pa, with a sputtering power of 30 W, a deposition time of 46.2 s, and a thickness of 5 nm. (2) Using the DC sputtering method, the power is 100W, at 3×10 -5 Under a vacuum degree of 1.3 Pa, a FeCrCoMoTi target with a mass ratio of Fe, Cr, Co, Mo and Ti of 42:30:25:2:1 was selected to deposit a FeCrCoMoTi nanofilm layer on the first Au layer with a deposition time of 1785.7 s and a thickness of 100 nm. (3) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a second Au layer was further deposited on the FeCrCoMoTi magnetic layer with a sputtering power of 30w, a deposition time of 46.2s, and a thickness of 5nm. (4) Using the DC sputtering method, at 3×10-5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCrCoMoTi layer, with a deposition time of 66.7 s, a sputtering power of 50 W, and a thickness of 5 nm. (5) After the deposition step is completed, the material obtained in step (4) is subjected to vacuum annealing. The annealing temperature is 650°C, the annealing time is 5 min, and the vacuum degree of the annealing environment is 5×10 -5 Pa.

[0022] After annealing, a magnetic code disk material containing a double Au catalytic magnetic layer film is obtained, with a coercive force of 552 Oe and a remanence of 8434 Oe.

[0023] Attached Figure 1 The MH curve (i.e., hysteresis loop) of the magnetic code disk material provided in this embodiment is shown in FIG. Figure 1 The MH curve provided shows in detail the whole process from the initial state (unmagnetized) to the saturation magnetization of the material provided in this embodiment, reflecting the response of the material to the external magnetic field.

[0024] From the attached Figure 1 It can be seen that the coercive force of the magnetic code disk material provided in Example 1 is 552 Oe; the remanence is 8434 Oe; and the saturation magnetic field strength is 10716 Oe.

[0025] Example 2 First, this embodiment provides a magnetic code disk material, which includes, from bottom to top: a double Au catalytic magnetic layer, which is obtained by vacuum annealing a first Au layer with a thickness of 10 nm, a FeCrCoMoTi layer of 100 nm, a second Au layer of 10 nm and a Ta layer with a thickness of 10 nm from bottom to top; the vacuum annealing temperature is 650°C.

[0026] The preparation method of the magnetic code disk material provided in this embodiment is: (1) 316 non-magnetic stainless steel code disc is selected as the metal substrate material (i.e., substrate). In a magnetron sputtering device, a DC sputtering method is used to deposit the code disc at 3×10 -5 The first Au layer was deposited on the substrate at a vacuum degree of Pa, with a sputtering power of 30 W, a deposition time of 92.4 s, and a thickness of 10 nm. (2) Using the DC sputtering method, the power is 100W, at 3×10 -5 Under the vacuum degree of Pa, FeCrCoMoTi target with the mass ratio of Fe, Cr, Co, Mo and Ti being 42:30:25:2:1 was used to deposit FeCrCoMoTi nanofilm layer on the first Au layer with a deposition time of 1785.7s and a thickness of 100nm. (3) Using the DC sputtering method, at 3×10-5 Under the vacuum degree of Pa, a second Au layer was further deposited on the FeCrCoMoTi magnetic layer with a sputtering power of 30w, a deposition time of 92.4s, and a thickness of 10nm. (4) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCrCoMoTi layer, with a deposition time of 133.4 s, a sputtering power of 50 W, and a thickness of 10 nm. (5) After the deposition step is completed, the material obtained in step (4) is subjected to vacuum annealing. The annealing temperature is 650°C, the annealing time is 5 min, and the vacuum degree of the annealing environment is 5×10 -5 Pa.

[0027] Comparative Example 1 First, this embodiment provides a magnetic code disk material, which includes, from bottom to top: a 100 nm FeCrCoMoTi layer and a 5 nm thick Ta layer obtained by vacuum annealing; the vacuum annealing temperature is 650°C.

[0028] First, this comparative example provides a magnetic code disk material, which includes, from bottom to top, a FeCrCoMoTi layer with a thickness of 100 nm and a Ta layer with a thickness of 5 nm. The magnetic code disk material is also subjected to vacuum annealing at 650° C.

[0029] The preparation method of the magnetic code disk material provided in this embodiment is: (1) A 316 non-magnetic stainless steel code disk was selected as the metal substrate material (i.e., substrate). In a magnetron sputtering device, a DC sputtering method was used with a power of 100 W at 3×10 -5 Under a vacuum degree of 1.3 Pa, a FeCrCoMoTi target with a mass ratio of Fe, Cr, Co, Mo and Ti of 42:30:25:2:1 was selected to deposit a FeCrCoMoTi nanofilm layer on the substrate with a deposition time of 1785.7 s and a thickness of 100 nm. (2) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCrCoMoTi layer, with a deposition time of 66.7 s, a sputtering power of 50 W, and a thickness of 5 nm. (3) After the deposition step is completed, the material obtained in step (2) is subjected to vacuum annealing. The annealing temperature is 650°C, the annealing time is 30 min, and the vacuum degree of the annealing environment is 5×10 -5 Pa.

[0030] After annealing, a magnetic code disk material containing a FeCrCoMoTi magnetic layer film is obtained, and its coercive force is 380 Oe and the remanence is 6423 Oe.

[0031] Attached Figure 2 The MH curve (i.e., hysteresis loop) of the magnetic code disk material provided in this comparative example is shown in FIG. Figure 2 The MH curve provided shows in detail the whole process from the initial state (unmagnetized) to the saturation magnetization of the material provided in this embodiment, reflecting the response of the material to the external magnetic field.

[0032] From the attached Figure 2 It can be seen that the coercive force of the magnetic code disk material provided in Comparative Example 1 is 380 Oe; the remanence is 6423 Oe; and the saturation magnetic field intensity is 7787 Oe.

[0033] Comparative Example 2 First, this embodiment provides a magnetic code disk material, which includes, from bottom to top: a 100nm FeCrCoMoTi layer and a 5nm thick Ta layer obtained by vacuum annealing; the specific method of vacuum annealing is: 700℃ vacuum annealing for 15min, followed by 630℃ vacuum annealing for 15min.

[0034] The preparation method of the magnetic code disk material provided in this embodiment is: (1) A 316 non-magnetic stainless steel code disk was selected as the metal substrate material (i.e., substrate). In a magnetron sputtering device, a DC sputtering method was used with a power of 100 W at 3×10 -5 Under a vacuum degree of 1.3 Pa, a FeCrCoMoTi target with a mass ratio of Fe, Cr, Co, Mo and Ti of 42:30:25:2:1 was selected to deposit a FeCrCoMoTi nanofilm layer on the substrate with a deposition time of 1785.7 s and a thickness of 100 nm. (2) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCrCoMoTi layer, with a deposition time of 66.7 s, a sputtering power of 50 W, and a thickness of 5 nm. (3) After the deposition step is completed, the material obtained in step (2) is subjected to vacuum annealing. The specific method of vacuum annealing is: vacuum annealing at 700°C for 15 minutes, followed by vacuum annealing at 630°C for 15 minutes. The vacuum degree of the annealing environment is 5×10 -5 Pa.

[0035] After annealing, a magnetic code disk material containing a FeCrCoMoTi magnetic layer film is obtained, with a coercive force of 455 Oe and a remanence of 7244 Oe.

[0036] Attached Figure 3 The MH curve (i.e., hysteresis loop) of the magnetic code disk material provided in this comparative example is shown in FIG. Figure 3The MH curve provided shows in detail the whole process from the initial state (unmagnetized) to the saturation magnetization of the material provided in this embodiment, reflecting the response of the material to the external magnetic field.

[0037] From the attached Figure 3 It can be seen that the coercive force of the magnetic code disk material provided in Comparative Example 2 is 455 Oe; the remanence is 7244 Oe; and the saturation magnetic field strength is 9021 Oe.

[0038] In summary, in combination with Example 1, Comparative Example 1 and Comparative Example 2, and the attached Figure 1 -Attached Figure 3 It is not difficult to see that compared with the FeCrCoMoTi magnetic code disk material, the magnetic code disk material provided in this application has excellent performance and simple processing. The coercive force of the FeCrCoMoTi film prepared by this method can reach 552 Oe, so that the subsequent code disk material prepared using this structure has higher performance. At the same time, the code disk signal has higher stability and anti-external interference ability after being written.

[0039] Although the description of the present application has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims by reference to the attached claims in view of the prior art, thereby effectively covering the intended scope of the present application. In addition, the above description of the present application is based on the foreseeable embodiments of the applicant, the purpose of which is to provide a useful description, and those non-substantial changes to the present application that have not yet been foreseen may still represent equivalent changes to the present application.

Claims

1. A magnetic code disk material, characterized in that: It comprises a double Au catalytic magnetic layer and a Ta layer; the double Au catalytic magnetic layer is obtained by vacuum annealing a first Au layer, a FeCrCoMoTi layer and a second Au layer from bottom to top; the vacuum annealing temperature is 645°C-655°C.

2. A magnetic code disk material according to claim 1, characterized in that: The thickness of the first Au layer is 5nm-10nm.

3. A magnetic code disk material according to claim 1, characterized in that: The thickness of the second Au layer is 5nm-10nm.

4. A magnetic code disk material according to claim 1, characterized in that: The thickness of the FeCrCoMoTi layer is 90nm-110nm.

5. The magnetic code disk material according to claim 1, characterized in that: The thickness of the Ta layer is 5nm-10nm.

6. The magnetic code disk material according to claim 1, characterized in that: The mass ratio of Fe, Cr, Co, Mo and Ti in the FeCrCoMoTi layer is 42:30:25:2:

1.

7. A method for preparing a magnetic code disk material according to any one of claims 1 to 6, characterized in that: The steps include: Prepare a substrate, perform DC sputtering on the substrate, and then perform vacuum annealing to obtain the magnetic code disk material; the DC sputtering includes the following processes: perform a first DC sputtering on the substrate to prepare the first Au layer, then perform a second DC sputtering to prepare the FeCrCoMoTi layer, then perform a third DC sputtering to prepare the second Au layer, and then perform a fourth DC sputtering to prepare the Ta layer.

8. The method for preparing a magnetic code disk material according to claim 7, characterized in that: The vacuum degree during the DC sputtering process is: 1×10 -5 Pa-3×10 -5 Pa; the first DC sputtering time is 46.2s, the second DC sputtering time is 1785.7s, the third DC sputtering time is 46.2s, and the fourth DC sputtering time is 66.7s.

9. The method for preparing a magnetic code disk material according to claim 7, characterized in that: The vacuum annealing conditions are 645° C.-655° C. and the time is 5 min-10 min.

10. A magnetic encoder, characterized in that: The magnetic code disk material comprises any one of claims 1-6.

Citation Information

Patent Citations

  • Magnetic code disc material, angular displacement magnetic sensor, high-speed motorized spindle of numerical control machine tool and preparation method of high-speed motorized spindle

    CN119372601A

  • Magnetic sensor

    JP2019086290A